Uma proposta no ensino de fração para adolescentes com e sem deficiência visual - Costa, Ailton Barcelos da (Universidade Federal de São Carlos, 2013)
The research deals with the teaching of fraction concepts to adolescents with and without visual impairment (blindness and low vision), from fourteen to eighteen. And understanding this as one of the bases for the study of mathematics itself, as well as the school experience as a privileged moment in the construction of citizenship, enabling the student to the complexity of the real world, this research arises from the need to expand scarce teaching experiences on this issue and on the specific difficulties of students of various grade levels to work with fractions. Starting from the presentation of the various experiences on teaching mathematics to visually impaired people in Brazil, since the nineteenth century until today, this study aimed to develop, implement and evaluate a procedure for teaching the concept of fractions to three adolescents with visual impairments which could also be used in teaching adolescents with visual sensory system integrity. The approach used was the differential, which focused on investigating the nature and causes of variations in the expression of learning in the population surveyed for this population that underwent evaluation of initial repertoire in two stages , followed by the application of teaching , prepared by the researcher , in two phases , with the final evaluation of repertoire and follow up. Finally, we discussed the educational backwardness of the participants, followed by an evaluation of the use of the general use of materials discrete and continuous, concluding that to investigate the oral and tactile stimulation to selected participants, we observed the formation of mathematical concepts through teaching fractions, both visually impaired teenagers and those with full vision. The objective of the research was achieved, demonstrating the need to rethink part of teaching and its mediation.
Keywords: Educação especial; Ensino de conceitos; Ensino de frações; Deficiência visual; Matemática inclusiva; Teaching concepts; Teaching fractions; Visual impairment; Inclusive mathematics; Special education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL